2023
DOI: 10.1186/s13287-023-03297-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells promote the repair of chemotherapy-induced premature ovarian failure by inhibiting granulosa cells apoptosis and senescence

Abstract: Background Chemotherapeutic drugs, particularly alkylating cytotoxics such as cyclophosphamide (CTX), play an important role to induce premature ovarian failure (POF). Hormone replacement therapy (HRT) is a widely used treatment to improve hormone secretion. However, the long-term HRT increases the risk of breast cancer and cardiovascular disease are attracting concerns. Therefore, there is an urgent need to develop a safe and effective treatment for POF. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Consistent with this, the ovaries harvested from adult mice administered cisplatin showed a senescent phenotype. These findings have been replicated by other groups 39,40 . Moreover, senotherapeutics targeting cellular senescence prevent this cisplatin‐induced ovarian injury and improve fertility, which is accompanied by a reduction in the number of senescent cells in the ovary 35 .…”
Section: Cellular Senescence In Pathological Conditions Of the Ovarymentioning
confidence: 66%
See 1 more Smart Citation
“…Consistent with this, the ovaries harvested from adult mice administered cisplatin showed a senescent phenotype. These findings have been replicated by other groups 39,40 . Moreover, senotherapeutics targeting cellular senescence prevent this cisplatin‐induced ovarian injury and improve fertility, which is accompanied by a reduction in the number of senescent cells in the ovary 35 .…”
Section: Cellular Senescence In Pathological Conditions Of the Ovarymentioning
confidence: 66%
“…These findings have been replicated by other groups. 39,40 Moreover, senotherapeutics targeting cellular senescence prevent this cisplatininduced ovarian injury and improve fertility, which is accompanied by a reduction in the number of senescent cells in the ovary. 35 The senotherapeutics used in this study were a combination of dasatinib and quercetin (DQ), metformin, and DQ plus metformin, and the results showed that DQ plus metformin was the most effective.…”
Section: Primary Ovarian Insufficiencymentioning
confidence: 99%
“…Generally speaking, after natural drying and using Swiss-Giemsa staining, according to the type and proportion of cells in the vaginal fluid (especially leukocytes, nucleated epithelial cells, and cornified squamous epithelial cells) that had been just collected by an optical microscope, we may infer which estrous phase the mice was in. Normally, the estrous cycle consists of 4 phases, including proestrus, estrus, metestrus, and diestrus 36 . Proestrus smears were dominated by nucleated epithelial cells, while estrus smears were predominantly composed of nucleated keratinocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have explored the mechanisms of action of hADSCs in POI, with paracrine regulation being frequently postulated [72,119,120]. These investigations suggest that downregulation of the phosphoinositide 3-kinases (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) axis and SMAD pathways contributes to the repair of chemotherapy-induced POI in ovaries.…”
Section: Adipose Tissue-derived Stem Cells (Adscs)mentioning
confidence: 99%